In vivo Functional Characterization of Hydrophilic X2 Modules in the Cellulosomal Scaffolding Protein - Tao, Xuanyu; Liu, Jiantao; Kempher, Megan L.; Xu, Tao; Zhou, Jizhong (Frontiers in Microbiology, 2022)
As part of free cellulases or scaffolding proteins in cellulosomes, the hydrophilic non-catalytic X2 module is widely distributed in cellulolytic Clostridia or other Frimicutes bacteria. Previous biochemical studies suggest that X2 modules might increase the solubility and substrate binding affinity of X2-bearing proteins. However, their in-vivo biological functions remain elusive. Here we employed CRISPR-Cas9 editing to genetically modify X2 modules by deleting the conserved motif (NGNT) from the cellulosomal scaffolding protein CipC in Clostridium cellulolyticum. Both single and double X2 mutants presented similar stoichiometric compositions in isolated cellulosomes as the wildtype strain (WT). These X2 mutants had an elongated adaptation stage during growth on cellulose compared to cellobiose. Compared to WT, the double mutant △X2-NC reduced cellulose degradation by 15% and the amount of released soluble sugars by 63%. Since single X2 mutants did not present such obvious physiological changes as △X2-NC, there seems to be a functional redundancy between X2 modules in CipC. The in vivo adhesion assay revealed that △X2-NC decreased cell attachment to cellulose by 70% but a weaker effect was also overserved in single X2 mutants. These results highlight the in vivo biological role of X2 in increasing cellulose degradation efficiency by enhancing the binding affinity between cells and cellulose, which provides new perspectives for microbial engineering.